Culinary MSMEs Fail to Protect Their Brands Due to Delays in Registration Decision Number 79/Pdt.Sus-HKI/Merek/2024/PN Niaga Jkt.Pst - Naftalia Prasetya; Siti Zahrania Maqdis (Business Management, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in the culinary sector are a key pillar of the Indonesian economy; however, many business owners neglect the legal protection of their intellectual assets, particularly trademarks. This paper examines the legal impact of the failure of culinary MSMEs to register their trademarks in a timely manner, which leads to disputes and financial losses. Using a qualitative case study of the Commercial Court Decision Number 79/Pdt.Sus-HKI/Merek/2024/PN Niaga Jkt.Pst, this research analyzes how Indonesia's trademark law system, which adheres to the first-to-file principle, grants supremacy of rights to the first registrant. The analysis shows that exclusive rights to a trademark arise from registration, not from prior use. The court rejected the arguments of "well-known mark" and "bad faith" submitted by the prior user due to a failure to present strong evidence in accordance with the procedural law of evidence. This ruling confirms that without registration, a business's legal standing is weak, even if it has built a brand reputation over a long time. In conclusion, legal certainty is only granted to parties who proactively register their trademarks with the Directorate General of Intellectual Property (DJKI). Therefore, early trademark registration is a crucial preventive step for culinary MSMEs to secure assets, avoid disputes, and strengthen their market position.